Cavernous Hemangioma of the Rib: A Rare Diagnosis - Stavros Gourgiotis; Anastasios Piyis; Nikolaos Panagiotopoulos; Panayotis Panayotopoulos; Nikolaos S. Salemis (Case Reports in Medicine)
Hemangioma of the rib is an uncommon benign vascular tumour. A case of rib hemangioma in a 29-year-old woman is presented. Chest roentgenogram and computed tomography revealed a mass along the inner surface of the 7th left rib with bone destruction. She underwent resection of the 7th rib. The pathologic diagnosis was cavernous hemangioma. Hemangiomas of the rib are rare tumours but should be kept in mind in the differential diagnosis of rib tumours.